Analysis of Human Resource Management Contribution to Economic Growth in Indonesia - Tantowi, Ahmad (Universitas Islam Kadiri, 2024)
Abstract This study uses data from 1990 to 2023 and the Generalized Method of Moments (GMM) and Autoregressive Distributed Lag (ARDL) approaches to examine how Human Resource (HR) management contributes to Indonesia's economic growth. The analysis's findings highlight the significance of investing in health and education by demonstrating that a rise in the Human Capital Index (HCI) raises GDP per capita both immediately and over time. Furthermore, economic growth is significantly boosted by rising GDP per capita, whereas rising unemployment and inflation have the opposite effect. Remittances from migrant workers are found to contribute positively to the economy, while an increase in CO2 emissions per capita has a negative impact. Larger forest areas and efficient and sustainable water use also support economic growth. The significance of policies that integrate education is emphasized by this study, health, employment, price stability, environment, and resources to achieve sustainable economic growth in Indonesia. Suggestions for further research include analysis with a wider data period and the addition of other variables such as technology and globalization to provide more comprehensive policy recommendations.